PERANCANGAN MEJA DAN KURSI BELAJAR DITINJAU DARI ASPEK ARGONOMIK - Peniarsih, Peniarsih; Sinaga, Dimpo (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2022)
The definition of human and computer interaction = a relationship between humans and computers that have certain characteristics to achieve a certain goal by running a system that is masked by an interface (interface). â€¢ The working principle of a computer = input-) process -) output .The computer is given data which is generally a series of numbers and letters. Then it is processed in a computer which becomes output according to human needs and desires. In aspects of life that must be done by every human being. With the increasing level of maturity of students, it is expected that students can play a role in society. The habits of students who have been very much an obstacle in the teaching and learning process are students who are less or not serious in learning due to inadequate learning facilities. For example, chairs and tables do not match the age level of students, the atmosphere of the room is not supportive, including poor lighting, very low noise levels and others. Therefore, a research is needed to redesign the table and chairs ergonomically, namely the design of tables and chairs by paying attention to comfort for the wearer. The tables and chairs used by school children today generally do not meet the ergonomic criteria, because the shape, design, and size are still very simple, and in the design process, factors related to Argonomics have not been considered.In meeting the design objectives or product design that is in accordance with the needs of school children, it is necessary to consider the dimensions of the children's bodies as the basis for measuring body dimensions. People generally never know what happens when data is entered into the CPU box via the keyboard. . Humans (users) are always focused on the monitor/printer as output. Humans are rarely aware of the process of interacting with computers. Humans only realize the interaction process when they find a problem and do not find a solution. Usually humans blame the interface that is less innovative, less attractive, less communicative Interaction can be said to be a dialogue between the user and the computerÂ Keywords: Ergonomki, Interaksi manusia dan computer